HETEROSIS STUDIES USING DIALLEL ANALYSIS FOR YIELD AND COMPONENT CHARACTERS IN MUNGBEAN (VIGNA RADIATA L. WILCZEK) - PUNAM S. YADAV, G. ROOPA LAVANYA, M. K. VISHWAKARMA, RAVI R. SAXESENA, D. K. BARANWAL SHWETA SINGH, (The Bioscan, 2015)
Twenty one hybrids of mungbean along with their seven parental lines in diallel fashion excluding reciprocal were studied to assess the extent of standard heterosis over standard check i.e. Samrat for yield and seven component characters. Out of 21 F1 hybrids, two crosses SML382 x WGG37 and PUSA9871 x WGG37 exhibited highly significant positive standard heterosis for number of clusters per plant, number of pods per cluster, number of pods per plant, number of seeds per pod, 100-seed weight and seed yield per plant. The hybrid SML382 X WGG37 was excelled for number of primary branches per plant. The crosses SML382 x WGG37 and PUSA9871 x WGG37 exhibited high standard heterosis for seed yield per plant which could be an excellent source for developing high yielding mungbean genotypes.